Bioequivalence Study of Two Long-Acting Formulations of Oxytetracycline Following Intramuscular Administration in Bovines - Mestorino, Nora; Marchetti, María Laura; Lucas, Mariana Florencia; Modamio, Pilar; Zeinsteger, Pedro; Fernández Lastra, Cecilia; Segarra, Ignacio; Mariño, Eduardo Luis (Frontiers in Veterinary Science, 2016)
The aim of this study was to evaluate the bioequivalence of two commercial long-acting formulations based on oxytetracycline hydrochloride between the reference formulation (Terramycin LA, Pfizer) and a test formulation (Cyamicin LA, Fort Dodge Saude Animal). Both formulations were administered in a single intramuscular route at a dose of 20 mg oxytetracycline per kg of body weigh in clinically healthy bovines. The study was carried out according to a one-period parallel design. Plasma samples were analysed by high-pressure liquid chromatography. The limit of quantitation was 0.050 µg /mL with an accuracy of 101.67 % with a CV of 13.15 %. Analysis of variance and 90% confidence interval tests were used to compare the bioavailability parameters (maximum plasma concentration, Cmax, and the area under the concentration time curve extrapolated to infinity, AUC0-∞) of both products. In the case of the time to maximum concentration (Tmax), non-parametric tests based on Wilcoxon’s signed rank test were preferred. The comparison of the mean AUC0-∞ values did not reveal any significant differences (311.40 ± 93.05 µg.h/mL and 287.71 ± 45.31 µg.h/mL, respectively). The results were similar for the Tmax (3.58 ± 0.90 h versus 3.42 ± 0.51 h). However, when comparing the mean Cmax some significant differences were found (8.73 ± 3.66 µg/mL and 10.43 ± 3.84 µg/mL, respectively). The 90 % confidence intervals for the ratio of AUC0-∞ and Tmax values for the reference and test product are within the interval 80-125 %, but the 90 % confidence intervals for the ratio of Cmax falls outside the proposed interval. It was concluded that Cmax of test product are not within the 20 % of those of the reference, thus suggesting that test oxytetracycline is not bioequivalent to the reference formulation.